2017
DOI: 10.1038/bjc.2017.208
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of copy number aberrations in microsatellite stable colon cancer in view of stromal component

Abstract: Background:Somatic copy number aberrations (CNAs) are common acquired changes in cancer cells having an important role in the progression of colon cancer (colorectal cancer, CRC). This study aimed to perform a characterisation of CNA and their impact in gene expression.Methods:Copy number aberrations were inferred from SNP array data in a series of 99 CRC. Copy number aberration events were calculated and used to assess the association between copy number dosage, clinical and molecular characteristics of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
113
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(118 citation statements)
references
References 37 publications
5
113
0
Order By: Relevance
“…Moreover, the majority of the specific altered chromosomal regions related with the four defined categories have been related with CRC and/or a higher risk of its development as well (e.g. gain on 8q24 or deletions on 1p21, 1p13 or 1p36) . But more remarkable are gains on 20q13 and deletions on 18p11, two of the most frequently altered regions in PM group, that have been already described by Di et al, presenting similarly within their sample of 15 SCRC patients, in which they defined that synchronous tumors were of different genetic origins, therefore polyclonal.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Moreover, the majority of the specific altered chromosomal regions related with the four defined categories have been related with CRC and/or a higher risk of its development as well (e.g. gain on 8q24 or deletions on 1p21, 1p13 or 1p36) . But more remarkable are gains on 20q13 and deletions on 18p11, two of the most frequently altered regions in PM group, that have been already described by Di et al, presenting similarly within their sample of 15 SCRC patients, in which they defined that synchronous tumors were of different genetic origins, therefore polyclonal.…”
Section: Discussionsupporting
confidence: 58%
“…gain on 8q24 or deletions on 1p21, 1p13 or 1p36). [37][38][39] But more remarkable are gains on 20q13 and deletions on 18p11, two of the most frequently altered regions in PM group, that have been already described by Di et al, 15 presenting similarly within their sample of 15 SCRC patients, in which they defined that synchronous tumors were of different genetic origins, therefore polyclonal.…”
Section: Discussionmentioning
confidence: 74%
“…Unlike glioma, where increased SCNA events were detected in high purity tumours, SCNAs in CC were not significantly associated with purity (16). In line with our findings, a recent report showed that for microsatellite stable (MSS) CC, stroma proportion was not correlated with SCNA events (40). As high stromal proportion may disturb the measurement of SCNAs, the correlation between tumour purity and SCNAs need to be further investigated.…”
Section: Discussionsupporting
confidence: 92%
“…In this algorithm, the expression characteristics of specific genes in immune cells and stromal cells are analyzed to calculate immune and stromal score to predict non-tumor cell invasion. Recent reports indicate that ESTIMATE is used in the study of prostate cancer (20), breast cancer (21), and colon cancer (22). However, the characteristics of the TME evaluated by ESTIMATE were not observed in the AML.…”
Section: Introductionmentioning
confidence: 99%